PENGARUH MODIFIKASI BOLA PLASTIK DALAM PEMBALAJARAN BOLAVOLI TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI 2 TORJUN - Siti Nur Hayati; Taufiq Hidayat (STAND, 2023)
The research objective was to find out whether and how much influence plastic ball modification had on volleyball learning on students' learning motivation at SMP Negeri 2 Torjun. This research method is a quantitative method with quasi-experimental research using a one-group pretest-pottest design. This study used the population as the sample in the study, namely class VIII SMP Negeri 2 Torjun with 75 students. The data collection procedure was carried out by the researcher by giving a learning motivation questionnaire, giving treatment or treatment then filling out a motivational study questionnaire again. Data analysis used the mean, standard deviation, normality test, t-test of similar samples, and percentages. The results showed that the learning motivation of students before being given treatment was 60.28% in the medium category. Then given treatment with a modified ball and again given a learning motivation questionnaire which showed a value of 86.75% included in the very high category. So that the percentage that there is an increase in the modification of plastic balls in volleyball learning on student learning motivation at SMP Negeri 2 Torjun with a percentage of 67% is in the high category.